1998
DOI: 10.2527/1998.7682032x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-associated antigen on bull sperm indicates fertility potential.

Abstract: A 30-kDa heparin-binding protein named fertility-associated antigen (FAA) was identified in sperm membranes of beef bulls with greater fertility potential. In a survey of 2,191 beef bulls, 88% had FAA present in sperm membranes (FAA-positive), and 12% were FAA-negative. In the first study, 54 Santa Gertrudis and 51 Santa Cruz bulls were grouped (1 to 14 bulls per group) according to FAA profiles and were bred to 2,403 cows at ratios of 1 bull: 25 cows. Fertility for 14 groups of FAA-positive bulls averaged 88%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 0 publications
4
47
0
4
Order By: Relevance
“…Absence or presence of a particular HBP in the seminal plasma may be associated with fertility potential of a bull. Presence of 31 kDa HBP (fertility associated antigen) showed better conception in cattle bull has been reported [25]. In the present study also, a 31 kDa HBP was more intensely present in bull no.…”
Section: Hbps Concentration and Electrophoretic Profilesupporting
confidence: 74%
“…Absence or presence of a particular HBP in the seminal plasma may be associated with fertility potential of a bull. Presence of 31 kDa HBP (fertility associated antigen) showed better conception in cattle bull has been reported [25]. In the present study also, a 31 kDa HBP was more intensely present in bull no.…”
Section: Hbps Concentration and Electrophoretic Profilesupporting
confidence: 74%
“…HBPs originate from the accessory sex glands and modulate heparin-sperm interactions that are indicative of fertility. Presence of three molecular weight HBP variants on sperm was previously associated with increased fertility potential of bulls (Bellin et al, 1996 and1998) and a targeted mutation in tudor domain-containing protein 1 led to male sterility because of postnatal spermatogenic defects (Chuma et al, 2006). Specifically, HBPs have been shown to play vital roles in spermatozoon survival, induction of sperm capacitation and the overall fertilization process, and any alteration in these proteins can be directly related to infertility (Miller et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified a seminal fluid, 30-kDA heparin-binding protein as a marker of bull fertility. This protein binds to sperm and was first named "Fertility Associate Antigen" and later identified as a DNAse I like protein (Bellin et al, 1996;Bellin et al, 1998). …”
Section: Discussionmentioning
confidence: 99%